Mortality from circulatory system diseases and low-level radon exposure in the French cohort study of uranium miners, 1946-1999 - Simon Nusinovici; Blandine Vacquier; Klervi Leuraud; Camille Metz-Flamant; Sylvaine Caër-Lorho; Alain Acker; Dominique Laurier (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: The few studies examining the risk of circulatory system diseases (CSD) associated with ionizing radiation have reported inconsistent results. Radon, a known pulmonary carcinogen, emits ionizing radiation. The aim of this study was to examine CSD mortality in a French cohort of uranium miners and evaluate the plausibility of an association with radon exposure. METHODS: The cohort included men employed as uranium miners for ≥1 year between 1946-1990. We obtained vital status and cause of death from national registers and reconstructed radon exposure for each year. Exposure-risk relations were estimated with a linear excess relative risk (ERR) model using a 5-year lag time. RESULTS: The cohort comprised 5086 miners, followed up for a mean duration of 30.1 years. The average cumulative exposure of the radon-exposed miners was 36.6 working level months (WLM). A total of 1411 deaths were observed, including 319 deaths due to CSD. No excess risk was found for this overall cause of death. A significant positive trend was observed between deaths from cerebrovascular diseases (CeVD) and cumulative radon exposure, together with a significant ERR per 100 WLM [ERR per 100 WLM 0.49, 95% confidence interval (95% CI) 0.07-1.23)]. Hard physical activity was identified as a potential modifying factor of the exposure-risk relation. CONCLUSIONS: For the first time in a cohort of uranium miners, our results suggest an association between CeVD mortality and cumulative radon exposure. Due to a lack of data, which limited our ability to assess possible confounding by cardiovascular risk factors, these findings should be interpreted with caution.